The Role of the Community in Mangrove Conservation in the Sea Waters of Poka Village, Teluk Ambon District, Ambon City - Kolengsusu, Ayuni Katri; Sihasale, Daniel Antoni; Riry, Johan (Jurnal Pendidikan Geografi Unpatti, 2024)
This study aimed to understand the role and level of community contribution in mangrove conservation efforts. The research method applied was qualitative research, using descriptive analysis and scoring techniques to describe the role and level of community participation in mangrove conservation efforts, involving 50 respondents as samples. The results of the study revealed that the role of the community in the preservation and maintenance of mangrove plants begins with the participation of the local community. Unfortunately, this participation is still relatively low in terms of mangrove maintenance. The level of community contribution to mangrove conservation in Poka Village reached 27%, and it is included in the moderate value category. Thus, the conclusion of this study shows that community participation in the preservation and maintenance of mangrove plants still needs to be improved, and their level of contribution to mangrove conservation is at a moderate level.